Consumo de bebidas energéticas en los estudiantes de medicina de la Universidad Nacional de Loja y sus efectos en el sistema nervioso central - Zapata Ambuludí, Jenny Alexandra (2015)
This researching: Consumption of the energetic drinks in the students of Medicine of the National University of Loja and its effects in Central Nervous System. Stating as main objective: To determine the effects on the Central Nervous System caused by the consumption of energetic drinks in the students of the third and sixth cycles on the Human Medicine Area of the National University of Loja. And as specific objectives: To establish the frequency, types of energetic drinks, reasons and effects from consumption of energetic drinks in the students of the third and sixth cycles of Medicine. The type of investigation is descriptive and transverse with the utilized of quantitative method. The study was carried out in the Human medicine Area of the National University of Loja, using a survey that was applied to 255 students in third and sixth of medicine. Men and women, between 19 and 24 years old At the end of the researching we can conclude that the 85% from the surveyed students accepted having consumed energetic drinks, 45% consume these drinks with more frequency in a month, 40% of the students consume during the exam period; and the opposite effect that mostly affects to the students is of a 28% Key words: energetic drinks, consumption, effects